Editorial Introduction: Children’s Food Practices and School Meals - Truninger, Mónica; Horta, Ana; Teixeira, José (The International Journal of Sociology of Agriculture and Food, 2014)
It is because of the synergetic character of food and its important relation with children and youth embodied practices, feelings and experiences that the guest editors of this special issue hosted the international conference ‘Food, Children and Youth: What’s Eating?’ in Lisbon in February 2014. The conference brought together scholars, researchers and practitioners from an array of disciplines within social sciences, public health and nutrition, from different countries within and outside Europe, and exploring disparate theoretical and methodological approaches to children’s food practices. The conference was organized under the remit of a Portuguese National Science Foundation funded project ‘Between School and Family: Children’s Food Knowledge and Eating Practices’ (PTDC/CS-SOC/111214/2009). This special issue is the result of a small selection of the excellent papers presented at the conference, and that could establish a fitting dialogue with the general theme and critical approach to children food practices and school meals that underscores this collection. Together, the articles reflect refined and complex insights in researching children’s food practices by focusing either on the contexts of situated and embodied practice or on the discourses that mediate such practices.